Are home environment injuries more fatal in children and the elderly?. Issue 6 (June 2022) - Banerjee, Niladri; Sharma, Naveen; Soni, Kapil Dev; Bansal, Varun; Mahajan, Anshul; Khajanchi, Monty; Gerdin Wärnberg, Martin; Roy, Nobhojit
Highlights: Contribution of home injuries (29% in hospital admissions) to the overall trauma burden of tertiary care hospitals is substantial and needs to be looked upon seriously. There is no significant difference in the overall mortality in patients sustaining injuries at home or sustaining injuries outside the home. Mortality in pediatric (<15 years) and the elderly (>64 years) patients are significantly higher if they are injured at home compared with outside the home. Most home injuries are preventable with simple and cost-effective strategies. The study highlights an urgent need for a public health policy for sustainable prevention strategies to lessen domestic/home injuries, especially in children and the elderly. Abstract: Introduction: 'In-home injuries' are those that occur within the house or its immediate surroundings. The literature on the prevalence and magnitude of home injuries is sparse. This study was designed to characterize the mechanisms of 'in-home' injuries and compare their outcomes with 'outside home injuries'. Materials and Methods: The Australia-India Trauma Systems Collaboration (AITSC) Project created a multicentric registry consisting of trauma patients admitted at four urban tertiary care hospitals in India from April 2016 to March 2018. This registry data was analysed for this study. All admitted patients except for dead on arrival were included. Patients were categorised into 'in-home' and 'outside home' cohorts based on the place where the trauma occurred. The outcome measures were 30 day in-hospital mortality and the length of hospital stay. Two subgroup analyses were performed, the first comprised pediatric patients (<15 years) and the second elderly patients >64 years). Results: Among 9354 patients in the AITSC data registry, 8398 patients were included in the study. Out of these, 29 percent were in-home injuries, whereas the rest occurred outside home. The 30 day in-hospital mortality was 10.6 percent in the 'in-home' cohort, as compared to 13.7 percent in the 'outside home' cohort. This difference although significant on univariable analysis ( p <0.01), there was no significant difference on multivariable regression analysis, after adjusting for age and injury severity score (OR = 0.88, 95% CI = 0.73–1.04; p  = 0.15). The length of hospital stay was shorter in the home injuries group (median = 5 days; IQR = 3–12 days) compared to the outside-home group (median = 7 days; IQR = 4–14 days) ( p < 0.01). In the pediatric and the elderly, on multivariable regression analysis, in-home injuries were associated with higher mortality than outside home injuries. Conclusion: There was no significant difference in the 30 day in-hospital mortality amongst admitted trauma patients sustaining injuries at home or outside the home. However, in pediatric and elderly patients the chances of mortality was significantly higher when injured at home.